2003
DOI: 10.1103/physrevb.68.134423
|View full text |Cite
|
Sign up to set email alerts
|

Hidden magnetic transitions in the thermoelectric layered cobaltite[Ca2CoO3]

Abstract: A positive muon spin rotation and relaxation (µ + SR) experiment on [Ca2CoO3]0.62[CoO2], (i.e., Ca3Co4O9, a layered thermoelectric cobaltite) indicates the existence of two magnetic transitions at ∼ 100 K and 400 -600 K; the former is a transition from a paramagnetic state to an incommensurate (IC) spin density wave (SDW) state. The anisotropic behavior of zero-field µ + SR spectra at 5 K suggests that the IC-SDW propagates in the a-b plane, with oscillating moments directed along the c-axis; also the IC-SDW i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 35 publications
6
89
0
Order By: Relevance
“…The Seebeck coefficient reaches a large value of 130 µV/K at around 150 K, and becomes almost temperature independent up to 400 K, as described within the modified Heikes formula in which the spin and orbital degrees of freedom of correlated Co 3d electrons are involved [20,21]. On the other hand, the Seebeck coefficient again increases with increasing temperature above 400 K, suggested to be associated with a spin-state crossover [12], but the hightemperature spin-state nature of Ca 3 Co 4 O 9 remains puzzling [22,23]. Note that the similar issue regarding an excited spin state is greatly debated in the perovskite LaCoO 3 [24][25][26][27].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The Seebeck coefficient reaches a large value of 130 µV/K at around 150 K, and becomes almost temperature independent up to 400 K, as described within the modified Heikes formula in which the spin and orbital degrees of freedom of correlated Co 3d electrons are involved [20,21]. On the other hand, the Seebeck coefficient again increases with increasing temperature above 400 K, suggested to be associated with a spin-state crossover [12], but the hightemperature spin-state nature of Ca 3 Co 4 O 9 remains puzzling [22,23]. Note that the similar issue regarding an excited spin state is greatly debated in the perovskite LaCoO 3 [24][25][26][27].…”
Section: Introductionmentioning
confidence: 86%
“…It is theoretically suggested that a mixture of low-spin and high-spin states may enhance the Seebeck coefficient [20]. Thus, a thermally-induced spinstate crossover from low-spin into higher-spin state is suggested for the enhancement of Seebeck coefficient [12], but the nature of spin states at high temperatures is still puzzling [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Ferrimagnetic or very weak ferromagnetic-like properties are also observed at low temperature [7]. In addition, µ + SR experiments have been interpreted with the presence of a spin density wave at low temperature [8], giving a clue for a gap opening near the Fermi level leading to the observed "Fermi liquid"-insulator transition. Nevertheless, the low temperature transport behavior is not really understood, specially because the ground state of the system is quite complex.…”
mentioning
confidence: 99%
“…[1,2,3,4,5] Several researchers reconfirmed later the existence of long-range magnetic order in the layered cobaltites by not only µ + SR [6] but also neutron diffraction experiments. [7] These cobaltites share a common structural component as a conduction path, i.e., the CoO 2 planes, in which a two-dimensional-triangular lattice of Co ions is formed by a network of edge-sharing CoO 6 octahedra.…”
Section: Introductionmentioning
confidence: 93%
“…On the contrary, it was found that not A TF but λ TF exhibit an anomaly at the spin state transition in the layered cobaltites. [3] Since each chain is considered to act as a single spin, we ignore the intra-chain 1D F interaction. Within the mean field theory, T N is expressed by; where z is the number of the nearest neighboring spins, J AF is the 2D AF coupling constant and k B is the Boltzmann constant.…”
Section: Figures 4(a) -4(d)mentioning
confidence: 99%